There is no random sampling in software engineering research - Amir, Bilal; Ralph, Paul (Proceedings of the 40th International Conference on Software Engineering: Companion Proceeedings, 2018)
Representative sampling is considered crucial for predominately quantitative, positivist research. Researchers typically argue that a sample is representative when items are selected randomly from a population. However, random sampling is rare in empirical software engineering research because there are no credible sampling frames (population lists) for the units of analysis software engineering researchers study (e.g. software projects, code libraries, developers, projects). This means that most software engineering research does not support statistical generalization, but rejecting any particular study for lack of random sampling is capricious.